Memantine increases the dendritic complexity of hippocampal young neurons in the juvenile brain after cranial irradiation - Zisiadis, Georgios Alkis; Alevyzaki, Androniki; Nicola, Elene; Rodrigues, Carlos F. D.; Blomgren, Klas; Osman, Ahmed M. (Frontiers in Oncology, 2023)
Introduction Cranial irradiation (IR) negatively regulates hippocampal neurogenesis and causes cognitive dysfunctions in cancer survivors, especially in pediatric patients. IR decreases proliferation of neural stem/progenitor cells (NSPC) and consequently diminishes production of new hippocampal neurons. Memantine, an NMDA receptor antagonist, used clinically to improve cognition in patients suffering from Alzheimer’s disease and dementia. In animal models, memantine acts as a potent enhancer of hippocampal neurogenesis. Memantine was recently proposed as an intervention to improve cognitive impairments occurring after radiotherapy and is currently under investigation in a number of clinical trials, including pediatric patients. To date, preclinical studies investigating the mechanisms underpinning how memantine improves cognition after IR remain limited, especially in the young, developing brain. Here, we investigated whether memantine could restore proliferation in the subgranular zone (SGZ) or rescue the reduction in the number of hippocampal young neurons after IR in the juvenile mouse brain. Methods Mice were whole-brain irradiated with 6 Gy on postnatal day 20 (P20) and subjected to acute or long-term treatment with memantine. Proliferation in the SGZ and the number of young neurons were further evaluated after the treatment. We also measured the levels of neurotrophins associated with memantine improved neural plasticity, brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF). Results We show that acute intraperitoneal treatment with a high, non-clinically used, dose of memantine (50 mg/kg) increased the number of proliferating cells in the intact brain by 72% and prevented 23% of IR-induced decrease in proliferation. Long-term treatment with 10 mg/kg/day of memantine, equivalent to the clinically used dose, did not impact proliferation, neither in the intact brain, nor after IR, but significantly increased the number of young neurons (doublecortin expressing cells) with radial dendrites (29% in sham controls and 156% after IR) and enhanced their dendritic arborization. Finally, we found that long-term treatment with 10 mg/kg/day memantine did not affect the levels of BDNF, but significantly reduced the levels of NGF by 40%. Conclusion These data suggest that the enhanced dendritic complexity of the hippocampal young neurons after treatment with memantine may contribute to the observed improved cognition in patients treated with cranial radiotherapy.